PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PEMANFAATAN KAIN PERCA SEBAGAI AKSESORIS MELALUI MEDIA YOUTUBE DI BENING SAGULING - Tsaniatu Zakiya (Comm-Edu (Community Education Journal), 2021)
The Bening Saguling is located on Jl. Babakan Cianjur, Kec. Cihampelas, Kab. West Bandung. Most of the people are housewives who do not work, with varying degrees of education, but most of them are junior and senior high school graduates. This is due to limited funds to continue to higher school levels, besides that there are other factors, namely the social structure factor that urges women to marry immediately at a young age which provides a great opportunity for women to become unproductive and only fully depend on their husbands who work as laborers. in a big city. The Bening Saguling NGO is a forum for the surrounding community to get training so that the community is able to improve the quality of life at large while still adhering to environmental preservation. The purpose of this research is to describe in more detail about women's empowerment through training on the use of patchwork as accessories through Youtube media in Bening Saguling. This study uses a descriptive method with a qualitative approach, which is the subject of this study, namely one training manager and 10 housewives. While the data collection technique is by means of observation, interview and documentation. The result of this training is to provide patchwork skills for low-educated women, providing a skill that can be of personal use and of sale value. The benefits of this activity are that the work can be sold so that it is expected to be able to improve the standard of living of the community and fill women's spare time with more useful activities.